2020
DOI: 10.3847/1538-4357/ab99a1
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin and Evolution of Curvature of the Spectral Energy Distribution of Fermi Bright Blazars

Abstract: The origin and evolution of spectral curvature in blazar spectral energy distribution (SED) is still unclear. Since the observed SED curvature is related to an intrinsic curvature in emitting electron energy distribution (EED), we study this question by employing a log-parabolic EED with a curvature parameter and peak energy to model the quasi-simultaneous broadband SEDs of selected blazars in the Fermi-LAT Bright AGN Sample using synchrotron and inverse Compton (IC) processes. We find that the log-parabolic I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…As a result, the rapid 𝛾-ray flares can be explained by the energetic and accelerated electrons (Γ 𝑒 = 2.25 ± .0.15) inside the highly magnetized (𝐵 = 4.14 G) and compact (𝑅 = 9 × 10 15 cm) emitting region. These values are similar to the estimated values obtained from previous studies of 4C 28.02 and other blazars (Zhang et al 2014;Zheng et al 2017;Anjum et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…As a result, the rapid 𝛾-ray flares can be explained by the energetic and accelerated electrons (Γ 𝑒 = 2.25 ± .0.15) inside the highly magnetized (𝐵 = 4.14 G) and compact (𝑅 = 9 × 10 15 cm) emitting region. These values are similar to the estimated values obtained from previous studies of 4C 28.02 and other blazars (Zhang et al 2014;Zheng et al 2017;Anjum et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Other researches also found anti-correlations between b and ν p (Tramacere et al 2007(Tramacere et al , 2009(Tramacere et al , 2011. Recently, Anjum et al (2020) found that BL Lacs show an anti-correlation between r of a log-parabolic EED and its peak energy γ p , which is a signature of stochastic acceleration. Particle acceleration mechanisms can produce the log-parabolic EED (see e.g., Kardashev 1962;Massaro et al 2004aMassaro et al , 2006Tramacere et al 2011;Chen 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Particle acceleration mechanisms can produce the log-parabolic EED (see e.g., Kardashev 1962;Massaro et al 2004aMassaro et al , 2006Tramacere et al 2011;Chen 2014). The intrinsic curvature r in the EED arises due to the combined effect of particle acceleration and radiative cooling (e.g., Anjum et al 2020). The anti-correlation between b and ν p might originate from that between r and γ p .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in Figure 1, the SED fitting result (total emission) using the log-parabolic electron spectrum is indicated by the long-dashed-dashed (blue) line, which exhibits a strong curvature in the Fermi GeV -ray band. In terms of intuitive phenomenology, the curvature-type radiation particle distribution may be more inclined to produce a curvature-type radiation photon spectrum (see Massaro et al 2004aMassaro et al ,b, 2006Anjum et al 2020); the broken-type radiation particle distribution may be more inclined to produce a broken-type radiation photon spectrum. Here, the curvature spectrum cannot effectively produce the -ray spectrum break (see Figure 1).…”
Section: −Ray Origin Of 3c 4543mentioning
confidence: 99%